ABDOMEN RADIOGRAPHY WITH SUSPENSION OF CORPUS ALIENU AT HAJI ADAM MALIK CENTRAL GENERAL HOSPITAL, MEDAN - Stephanie Ariyanti; Justinus Tambunan (Journal of Public Health Science, 2025)
Abdominal radiography with suspected swallowed foreign body can be defined as an abdominal examination for a sudden condition in the form of a foreign object in the abdominal cavity that requires immediate action. Foreign body is a common cause of emergency unit visits and can enter the human body through various methods, namely by swallowing, inhalation, and intentional insertion. Foreign body can occur at all ages, especially children because they often put objects into their mouths. This study aims to find out how to perform an abdominal examination with suspected foreign body where the patient is a child. The projections used are Antero-Posterior Erect and Lateral, which can show the anatomy and location of the foreign body in the abdominal cavity. The type of research carried out is a qualitative research method, with data collection techniques based on observation results. The results of the study obtained abdominal radiographic examination with suspected foreign body with film processing carried out using Digital Radiography (DR).